Different models of the relationship between women’s fertility and employment - BELATTAR Loubna; ELBOUANABI Maroi; ASRAOUI Imane; TORRA Mohamed; ELHAMMA Azzouz (African Scientific Journal, 2025)
Abstract This article examines the complex relationship between women’s employment and fertility, a central topic in labor and family economics. The analysis draws on economic and sociological theoretical frameworks to understand the factors influencing women’s choices between career and family life. The multidimensional nature of this relationship is highlighted through the study of economic, sociocultural, and institutional contexts, which vary across regions and time periods. The study employs classical economic theories, notably Becker’s model based on opportunity costs, as well as sociological approaches such as Parsons’ social role theory and Kergoat’s concept of the "double workday." These different theoretical perspectives allow for an analysis of how gender norms and societal expectations influence women’s decisions regarding fertility and employment. The empirical results reveal nuanced conclusions. While some studies establish a negative correlation between female employment and fertility, others identify contexts where these two dimensions coexist harmoniously, particularly through favorable family policies, egalitarian ideologies, and efficient childcare systems. Recent models, incorporating dynamic and stochastic approaches, help refine these analyses by taking into account labor market structures, individual preferences, and the impact of public policies. The originality of this research lies in its interdisciplinary approach, combining economic and sociological perspectives to provide a more comprehensive understanding of the work-fertility relationship. Furthermore, its value stems from the integration of contemporary dynamic modeling techniques that offer new insights for policymakers seeking to support both women’s employment and fertility goals. Keywords: Fertility, Women’s Employment, Public Policies, Opportunity Costs